Mentoring-Career Development - Scheef, Devon; Kaye, Beverly (Association for Talent Development, 2000)
Here are three approaches you can use to install this powerful mentoring and performance improvement tool in your organization. Use the detailed descriptions of one-on-one mentoring, group mentoring, and virtual mentoring, advice on mentor selection and strategies for success. A mentoring program planner is also included.